CONTENT AND CONCEPTUAL BASIS OF THE CONCEPT OF DOMESTIC VIOLENCE (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical and methodological foundations of the philosophical and anthropological analysis of the gender identity factor in preventing domestic violence, the philosophical aspects of ensuring gender identity in preventing domestic violence, advanced foreign experiences and priority areas, and future tasks. It also analyzes the theoretical and methodological aspects of the philosophical and anthropological analysis of the gender identity factor in preventing domestic violence.